Considerations on the use of modern biotechnical methods in agriculture: sexual pheromone traps (Bollettino di zoologia agraria e bachicoltura, 2024)
The present use of sexual pheromone traps in modern agricultural defence methodology does not always provide wholly valid data for the prediction and prevention of damage.The reasons for this are numerous: in particular these modern biotechnical methods are sometimes improperly used; and only one standard type of trap is available, which may not be optimal for all environmental conditions.